Traditional Habits in Efforts to Preserve Underwater Ecosystems to Support Tourism on Jemeluk Beach, Purwakerti Village, Abang District, Regency Karangasem - I Kadek Ari Putra (Fakultas Hukum, Universitas Warmadewa, 2024)
Purwakerti Village, Abang District, Karangasem Regency's Jemeluk Beach is well known for its diverse and abundant underwater natural beauty. Nonetheless, the viability of the undersea ecology is threatened by the quick growth of tourism. Local people have great potential to help preserve these ecosystems through their traditional knowledge and habits, such as sustainable fishing methods. In managing the underwater ecosystem at Jemeluk Beach, this research seeks to integrate the philosophical values of local wisdom and customs. It also optimizes the role of fishing communities in accomplishing the goal of sustainable ecosystem preservation within the framework of tourism development. The research method uses a normative legal approach with literature studies from primary, secondary, and tertiary legal materials. The research results show that the integration of traditional community knowledge with modern science can create an effective and sustainable conservation strategy. Environmental education, active participation of local communities, and implementation of environmentally friendly technologies are some of the strategies proposed to achieve these goals. In conclusion, further education and training, as well as cooperation between local communities, and governmental and non-governmental groups, can help preserve the underwater ecology at Jemeluk Beach. Promoting responsible and sustainable tourism development can enhance the economic well-being of nearby communities in addition to promoting environmental sustainability.